On the dynamics of work identity in atypical employment: setting out a research agenda. Issue 3 (4th May 2018) - Selenko, Eva; Berkers, Hannah; Carter, Angela; Woods, Stephen A.; Otto, Kathleen; Urbach, Tina; De Witte, Hans
ABSTRACT: Starting from the notion that work is an important part of who we are, we extend existing theory making on the interplay of work and identity by applying them to (so called) atypical work situations. Without the contextual stability of a permanent organizational position, the question "who one is" will be more difficult to answer. At the same time, a stable occupational identity might provide an even more important orientation to one's career attitudes and goals in atypical employment situations. So, although atypical employment might pose different challenges on identity, identity can still be a valid concept to assist the understanding of behaviour, attitudes, and well-being in these situations. Our analysis does not attempt to "reinvent" the concept of identity, but will elaborate how existing conceptualizations of identity as being a multiple (albeit perceived as singular), fluid (albeit perceived as stable), and actively forged (as well as passively influenced) construct that can be adapted to understand the effects of atypical employment contexts. Furthermore, we suggest three specific ways to understand the longitudinal dynamics of the interplay between atypical employment and identity over time: passive incremental, active incremental, and transformative change. We conclude with key learning points and outline a few practical recommendations for more research into identity as an explanatory mechanism for the effects of atypical employment situations.